Bibliometric and visualized analysis of electroacupuncture in the past 10 years. (October 2022) - Wei, Jinqiang; Yang, Zihong; Lin, Qiutian; Xu, Haiyan; Lai, Fang; Han, Yun; Li, Jun; Cui, Shuai
Abstract: Background: There are many studies that have interrogated the evolution and use of electroacupuncture (EA). We aimed to evaluate the research status, cooperation and development of EA in the past 10 years. Methods: We obtained data on the EA from the Web of Science core collection database. CiteSpace 5.7. R1 software was used to assess research cooperation through analysis of authors, institutions and countries. In addition, keyword cluster analysis, references and burst detection were analyzed to explore research hotspots and trends in the field of EA. Results: We included a total of 3019 citing literature and 78, 235 cited literature for analysis. The data showed that there has been a rise in the global number of EA studies in the past decade. Besides, the data demonstrated that China has made outstanding contribution in the development of EA. Whereas there is inter-agency cooperation in China, there is less cooperation with other countries. In addition, we showed frequent use of keywords such as "expression", "stimulation", or "pain". Besides, neuroscience was the main research area, followed by general medicine and oncology. Furthermore, with the improved research methods and technologies, there is enhanced overall quality of the studies. Conclusion: Taken together, our findings demonstrate a steady increase in the studies involving EA. However, the studies are unevenly distributed among countries and thus there is need for closer international cooperation. Highlights: In the past decade, there has been a rise in the global number of electroacupuncture studies. The basic and clinical research of cardiovascular, cerebrovascular and pain diseases are hot spots. There is more need for broad and close cooperation in this field around the world.